1998
DOI: 10.1016/s0304-3959(98)00021-9
|View full text |Cite
|
Sign up to set email alerts
|

Same incidence of adverse drug events after codeine administration irrespective of the genetically determined differences in morphine formation

Abstract: The analgesic effect and adverse events of the weak opioid codeine is assumed to be mediated by its metabolite morphine. The cytochrome P-450 enzyme CYP2D6 catalysing the formation of morphine exhibits a genetic polymorphism. Two distinct phenotypes, the extensive (EMs) and poor metabolisers (PMs), are present in the population. The prevalence of PMs in the Caucasian population is 7% to 10%. Since PMs do not express functional CYP2D6, they have a severely impaired capacity to metabolise drugs which are substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
153
0
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(167 citation statements)
references
References 10 publications
6
153
0
8
Order By: Relevance
“…Thus, the pharmacological effects of dihydrocodeine may be lower in poor metabolizers and more pronounced in ultrarapid metabolizers. Corresponding results have been reported for the effects of codeine depending on the formation of its metabolite morphine via CYP2D6 (Poulsen et al 1996;Eckhardt et al 1998) but these are not unequivocal (Vree et al 2000). Results concerning dihydrocodeine were also contradictory (Fromm et al 1995;Jurna et al 1997;Wilder-Smith et al 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the pharmacological effects of dihydrocodeine may be lower in poor metabolizers and more pronounced in ultrarapid metabolizers. Corresponding results have been reported for the effects of codeine depending on the formation of its metabolite morphine via CYP2D6 (Poulsen et al 1996;Eckhardt et al 1998) but these are not unequivocal (Vree et al 2000). Results concerning dihydrocodeine were also contradictory (Fromm et al 1995;Jurna et al 1997;Wilder-Smith et al 1998).…”
Section: Discussionmentioning
confidence: 82%
“…However, children who are poor metabolizers (up to one-third of the population) 2 convert very little codeine, leading to inadequate symptom relief. 3 More concerning, ultra-rapid metabolizers convert 5 to 30 times more than is typical, which can lead to fatal toxicity. 1 Case reports describe over a dozen fatalities associated with standard doses of codeine in ultra-rapid metabolizers, 4 and the ethnic subpopulation prevalence of this phenotype ranges from 2% to 40%.…”
Section: Discussionmentioning
confidence: 99%
“…A study on analgesic effects in nine PMs and nine EMs reported analgesic effects only in EMs but the same incidence of adverse drug effects in both groups. 36 Opioid effects also depend on biotransformation within the brain, and, thus, concentrations of codeine, norcodeine and C6G in the brain might differ from those observed in plasma. Recently, a functional variant of CYP2D7 leading to expression of this pseudogene in brain and to brain metabolism of codeine to morphine has been described in four of eight individuals of whom brain autopsies were obtained.…”
Section: Discussionmentioning
confidence: 99%